A new energy transfer channel from carotenoids to chlorophylls in purple bacteria - Jin Feng (Nature Portfolio, 2017)
Carotenoids harvest energy from light and transfer it to chlorophylls during photosynthesis. Here, Feng et al. perform ab initio calculations on excited-state dynamics and simulated 2D electronic spectrum of carotenoids, supporting the existence of a new excited state in carotenoids.